Reconstruction of Notaries Liability on Their Authentic Deed Based on Justice Value: Moderating Role of Supply Chain Management - Anis Mashdurohatun; Belahim . (International Journal of Supply Chain Management, 2020)
Notaries’ liability for the authentic deed they draw must be based on the concept of a Notary Public as a position. This concept means were as long as the Notaries still have authority to do the deed, the liability for the make of deed is attached to and imposed on him. This study uses socio-legal approach, in which in this context, legal institutions are not understood as normative entities, but will be seen as part of the whole social system that is in an interrelated condition with other social variables. The result of this research is that the liability principle of a notary which is used is based on mistakes liability. The results also conclude that supply chain management (information facilitation) system acts as a positive moderator in the relation. Notaries can be held liable if there is an element of error they did. Noting the provisions of Article 65 of the Law on Notary Position, the retired Notaries Public will remain responsible for the deed they made. Therefore, there is confusion about the limit of Notaries liability based on Article 65 of the Notarial Law (UUJN) that even though all the deeds made by the Notaries have been handed over or transferred to the Notary protocol depositor, and even they have stopped or not served any longer as Notaries, they must still be responsible for the liability as notaries for their entire lives.